2019
DOI: 10.1016/j.jand.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Sugar-Sweetened Beverage Intakes Are Longitudinally Associated with Higher Body Mass Index z Scores in a Birth Cohort Followed 17 Years

Abstract: Background: Sugar-sweetened beverages (SSB) are considered a risk factor for obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
3
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 42 publications
3
38
3
12
Order By: Relevance
“…Our lack of association of SSB consumption frequency with subsequent BMI z-score or other measures of adiposity differs from an observational study [29] and meta-analyses of observational studies largely from Western settings [5,6,30,31]. A cohort study conducted in US children suggested that BMI z-score was 0.050 higher (95% CI 0.022 to 0.079) for each additional 8 oz/day of SSB consumed at ages 2 to 17 years [29]. The discrepancy between our study and that of Marshall et al [29] may be because the participants in our study had a much lower SSB intake (6.8% consumed SSB daily at 11 years) than those in that study (median 8 oz/day at 11 years).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our lack of association of SSB consumption frequency with subsequent BMI z-score or other measures of adiposity differs from an observational study [29] and meta-analyses of observational studies largely from Western settings [5,6,30,31]. A cohort study conducted in US children suggested that BMI z-score was 0.050 higher (95% CI 0.022 to 0.079) for each additional 8 oz/day of SSB consumed at ages 2 to 17 years [29]. The discrepancy between our study and that of Marshall et al [29] may be because the participants in our study had a much lower SSB intake (6.8% consumed SSB daily at 11 years) than those in that study (median 8 oz/day at 11 years).…”
Section: Discussioncontrasting
confidence: 99%
“…The discrepancy between our study and that of Marshall et al [29] may be because the participants in our study had a much lower SSB intake (6.8% consumed SSB daily at 11 years) than those in that study (median 8 oz/day at 11 years). Notably, Marshall et al also found a positive association of water/sugar-free beverages with BMI z scores [29], thus confounding may exist. In the US, both SSB intake and adiposity are strongly associated with socio-economic position, which could confound the estimates [15,16].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Many causal questions unique to paediatric populations involve understanding effects of time-varying continuous (multi-level) pre-and postnatal exposure interventions on later offspring outcomes. For example, sugar-sweetened beverage (SSB) consumption is associated with weight gain in childhood and adulthood, [1][2][3] and randomised interventions that reduce SSB consumption in 4-to 11-year-olds and in adolescents demonstrated short-term weight loss. 4,5 Given possible developmental programming of body weight, 6,7 there is interest in understanding whether reducing SSB consumption in certain windows of early life leads to lower body mass index (BMI) in adolescence.…”
Section: Backg Rou N Dmentioning
confidence: 99%